Glutamine Supplementation in Sick Children: Is It Beneficial? - Elise Mok; Régis Hankard (Journal of Nutrition and Metabolism)
The purpose of this review is to provide a critical appraisal of the literature on Glutamine (Gln) supplementation in various conditions or illnesses that affect children, from neonates to adolescents. First, a general overview of the proposed mechanisms for the beneficial effects of Gln is provided, and subsequently clinical studies are discussed. Despite safety, studies are conflicting, partly due to different effects of enteral and parenteral Gln supplementation. Further insufficient evidence is available on the benefits of Gln supplementation in pediatric patients. This includes premature infants, infants with gastrointestinal disease, children with Crohn's disease, short bowel syndrome, malnutrition/diarrhea, cancer, severe burns/trauma, Duchenne muscular dystrophy, sickle cell anemia, cystic fibrosis, and type 1 diabetes. Moreover, methodological issues have been noted in some studies. Further mechanistic data is needed along with large randomized controlled trials in select populations of sick children, who may eventually benefit from supplemental Gln.